Evolution of the mammalian middle ear and jaw: adaptations and novel structures. Issue 1 (11th June 2012) - Anthwal, Neal; Joshi, Leena; Tucker, Abigail S.
Abstract Having three ossicles in the middle ear is one of the defining features of mammals. All reptiles and birds have only one middle ear ossicle, the stapes or columella. How these two additional ossicles came to reside and function in the middle ear of mammals has been studied for the last 200 years and represents one of the classic example of how structures can change during evolution to function in new and novel ways. From fossil data, comparative anatomy and developmental biology it is now clear that the two new bones in the mammalian middle ear, the malleus and incus, are homologous to the quadrate and articular, which form the articulation for the upper and lower jaws in non‐mammalian jawed vertebrates. The incorporation of the primary jaw joint into the mammalian middle ear was only possible due to the evolution of a new way to articulate the upper and lower jaws, with the formation of the dentary‐squamosal joint, or TMJ in humans. The evolution of the three‐ossicle ear in mammals is thus intricately connected with the evolution of a novel jaw joint, the two structures evolving together to create the distinctive mammalian skull.